Friction and wear of Ni3Al-based composites containing Ag and Cu modified hBN at elevated temperatures - Mahto N.K.; Shafali K.; Tyagi R.; Sharma O.P.; Khatri O.P.; Sinha S.K. (My University, 2025)
Ni3Al-based composite containing Ag/Cu modified hBN nanosheets (Cu-hBN)/Ag-Cu-hBN have been fabricated by vacuum hot press sintering and their tribological performance has been evaluated at RT, 200, 400, 600 and 800 °C at a constant load of 10 N and a sliding speed of 0.2 m/s using a ball-on-disc rotary tribometer against a Si3N4 ball. The main aim of the study is to examine the occurrence of a synergetic action between Ag and Cu-hBN in attaining low friction and anti-wear properties from room temperature to 800 °C. The results indicated a significant reduction in the coefficient of friction by the addition of a combination of Ag and Cu-hBN in comparison to either Ag or Cu-hBN. Ni3Al-Ag-Cu-hBN attained the lowest coefficient of friction (∼0.19) and wear rate (1.85 x 10-5 mm3/Nm) at 800 °C, which has been ascribed to the supportive lubrication provided by Ag and Cu-hBN. The investigation also revealed that Ag provided lubrication at temperatures below 500 °C, whereas Cu-hBN and other lubricious oxides like Ag2MoO4, Ag2Mo2O7, MoO3, CuO and NiMoO4 provided low friction and anti-wear properties beyond 500 °C. Self-lubricating Ni3Al-Ag-Cu-hBN composites offer themselves as a potential candidate for high-temperature applications where the components work under relative sliding motion. © 2023 Elsevier B.V.